PENGENALAN KONSEP GEOMETRI PADA ANAK USIA 5-6 TAHUN DI TK ISLAM AL-AZHAR 21 PONTIANAK - Ainunnissa, Shereen Regina; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study is to describe the plan of learning the introduction of geometry concept, the implementation of learning geometry concept, the evaluation carried out by the teacher in learning the introduction of geometry concept and the obstacles experienced by the teacher in introducing geometry concept to the students aged 5-6 years at the Islamic Kindergarten Al-Azhar 21 Pontianak. This research was conducted using a descriptive method with a qualitative approach, in which the research data were presented in the form of a description instead of numbers. As for the data sources, there were 2 teachers consisting of a class teacher and an assistant teacher as well as the students of B1 AL-QUDDUS at Islamic Kindergarten AL-Azhar 21 Pontianak. The techniques of data collection used by the researcher were direct observation, interview, and documentary study techniques with collecting tools were interview guides, observation guides, and documentation. The results of the study shown that the introduction of geometry concept went well and was carried out in accordance with the RKH. Through the introduction of geometry concept, the students are able to recognize geometric shapes and objects in the form of geometry.